VDR Gene Single Nucleotide Polymorphisms and Autoimmunity: A Narrative Review - Cristina Agliardi; Franca Rosa Guerini; Elisabetta Bolognesi; Milena Zanzottera; Mario Clerici (Biology, 2023)
The vitamin D/Vitamin D receptor (VDR) axis is crucial for human health as it regulates the expression of genes involved in different functions, including calcium homeostasis, energy metabolism, cell growth and differentiation, and immune responses. In particular, the vitamin D/VDR complex regulates genes of both innate and adaptive immunity. Autoimmune diseases are believed to arise from a genetic predisposition and the presence of triggers such as hormones and environmental factors. Among these, a role for Vitamin D and molecules correlated to its functions has been repeatedly suggested. Four single nucleotide polymorphisms (SNPs) of the VDR gene, ApaI, BsmI, TaqI, and FokI, in particular, have been associated with autoimmune disorders. The presence of particular VDR SNP alleles and genotypes, thus, was observed to modulate the likelihood of developing diverse autoimmune conditions, either increasing or reducing it. In this work, we will review the scientific literature suggesting a role for these different factors in the pathogenesis of autoimmune conditions and summarize evidence indicating a possible VDR SNP involvement in the onset of these diseases. A better understanding of the role of the molecular mechanisms linking Vitamin D/VDR and autoimmunity might be extremely useful in designing novel therapeutic avenues for these disorders.